Numerical Modeling of Thermal-Dependent Creep Behavior of Soft Clays under One-Dimensional Condition - Qi-Yin Zhu; Ping Qi (Advances in Civil Engineering)
Creep is a common phenomenon for soft clays. The paper focuses on investigating the influence of temperature on the time-dependent stress-strain evolution. For this purpose, the temperature-dependent creep behavior for the soft clay has been investigated based on experimental observations. A thermally related equation is proposed to bridge the thermal creep coefficient with temperature. By incorporating the equation to a selected one-dimensional (1D) elastic viscoplastic (EVP) model, a thermal creep-based EVP model was developed which takes into account the influence of temperature on creep. Simulations of oedometer tests on reconstituted clay are made through coupled consolidation analysis. The bonding effect of the soil structure on compressive behavior for intact clay is studied. By incorporating the influence of the soil structure, the thermal creep EVP model is extended for intact clay. Experimental predictions for thermal creep oedometer tests are simulated at different temperatures and compared to that obtained from reconstituted clay. The results show that the influence of temperature on the creep behavior for intact clay is significant, and the model, this paper proposed, can successfully reproduce the thermal creep behavior of the soft clay under the 1D loading condition.